Relationship between environmental factors and plankton in the Bayuquan Port, Liaodong Bay,China：a five-year study - 宋伦 杨国军 王年斌 鲁晓倩 (Chinese journal of oceanology and limnology, 2016)
To understand the relationship between the plankton community and environmental factor and water quality in the Bayuquan Port of Liaodong Bay, China, and investigations were carried ou during six dif ferent periods（April 2009, April 2010, October 2011, April 2012, October 2012, and Apri 2013）. This area was characterized by high levels of nutrient and suspended solids（SPS） during surve periods, and eutrophication led to the occurrence of red tides in April and October 2012 and April 2013 Our analyses revealed that the plankton communities of Bayuquan Port lacked stability and were af fecte seriously by external disturbance（e.g., oceanographic engineering and river runof f）. Our data indicate tha oil, dissolved inorganic nitrogen（DIN）, SPS, and chlorophyll a（Chl- a） were key factors that regulated th phytoplankton and zooplankton communities. The partial redundancy analysis（partial RDA） suggested tha oil and SPS were the most important environmental variables af fecting the phytoplankton community i April 2010 and 2012, whereas DIN concentration played a governing role in zooplankton dynamics. Oi and Chl-a concentrations af fected signifi cantly the zooplankton community in October 2012. Therefore, th plankton communities could refl ect both dynamic changes in coastal environmental factors and the ongoin eutrophication process caused by anthropogenic activities in this area.